Frederick A. de Armas, Cervantes, Raphael and the Classics. Cambridge University Press, Cambridge, 1998; 241 pp. (Cambridge Studies in Latin American and Hispanic Literature, 12). - Alan Soons (Nueva Revista de Filología Hispánica, 2001)
Se reseñó el libro: Cervantes, Raphael and the Classics.